2023
DOI: 10.1038/s41598-023-30698-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermented soybean meal supplementation on the growth performance and apparent total tract digestibility by modulating the gut microbiome of weaned piglets

Abstract: This study investigates the effects of soybean meal fermented by Enterococcus faecium as a replacement for soybean meal on growth performance, apparent total tract digestibility, blood profile and gut microbiota of weaned pigs. Eighty piglets (weaned at 21 days) [(Landrace × Yorkshire) × Duroc] with average body weight of 6.52 ± 0.59 kg) were selected and assigned to 4 treatments/4 replicate pens (3 barrows and 2 gilts). The four diets (SBM, 3, 6 and 9% FSBM) were formulated using fermented soybean meal to rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 74 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…These compounds acted antagonistically against other microorganisms, inhibiting the growth of contaminants. A similar study indicated that fermented soybean meal can improve the growth performance of weaned pigs by inhibiting the growth of harmful bacterial populations 25 …”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…These compounds acted antagonistically against other microorganisms, inhibiting the growth of contaminants. A similar study indicated that fermented soybean meal can improve the growth performance of weaned pigs by inhibiting the growth of harmful bacterial populations 25 …”
Section: Resultsmentioning
confidence: 91%
“…The FSBM was subjected to fermentation at different environmental temperatures (15,25,30,35, 40 and 45 °C). The internal fermentation temperature of the SBM was measured every 2 h during the fermentation process.…”
Section: Measurement Of Fermentation Heat Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary eubiotic supplements could stimulate the growth of beneficial bacteria and minimize pathogenic bacteria activity in the poultry gut. Alpha diversity could serve as an indicator of the functional resilience of the intestinal microbial ecosystem, including species richness (Observed species and Chao1) and species diversity (Shannon, Simpson and Pielous evenness) [ 41 , 42 ]. MR increased observed species and Chao1 index and MRPG increased Shannons index in the ileum sample of broilers compared with NC group.…”
Section: Discussionmentioning
confidence: 99%
“…Muniyappan et al . (2023) concluded that growth performance, apparent total digestibility and blood status of weaned piglets were improved after replacing soybean meal with fermented soybean meal. Similarly, Abdel‐Raheem et al .…”
Section: Application Of Fermented Soybean Mealmentioning
confidence: 99%